PENURUNAN LUAS AREA MATA DAN NON-DETACHMENT TAIL PADA EMBRIO IKAN ZEBRA (Danio rerio) AKIBAT PAPARAN CADMIUM CHLORIDE (CdCl2) - Erfina Daniati (Jurnal Kedokteran Komunitas (Journal of Community Medicine), 2019)
Introduction: Nowadays, a lot cadmium emitted to the environment source by pesticide, the deportation of industry waste, and tobacco cigarettes. The exposure of cadmium for pregnant woman in the long period of time will be accumulated in human’s body causing terratogenic effect on fetus. This research proposed to identify terratogenic effect on zebrafish (Danio rerio) embryo (F2) that the parental (F1) exposure by cadmium chloride (CdCl2) chronically.Method: This research used laboratory experiment by in vivo post-test only. The experimental animal was Danio rerio (F1) that was exposured for 30 days. Observation area of eyes and non-detachment tail in Danio rerio embryo (F2) using stereo microscope with the 4,5x magnification and analyzed with software Image J. Data analysis done by One Way ANOVA and continued by Least Significant Difference (LSD) using software Statistical Product and Service Solution (SPSS) 16.0 version.Findings: The higher CdCl2 dose being exposure by Danio rerio parental (F1), influence the greater impact of the derease area of eyes and the length non-detachment tail on Danio rerio embryo (F2). Found that the mean decrease area of eyes for control, exposure of CdCl2 dose 0.5, 1, and 1.5 ppm is around 0,027 ± 0,002 mm, 0,022 ± 0,002 mm, 0,017 ± 0,002 mm, and 0,010 ± 0,002 mm respectively. The mean decrease of length non-detachment tail for control, exposure of CdCl2 dose 0.5, 1, and 1.5 is around 0,154 ± 0,017 mm, 0,128 ± 0,011 mm, 0,086 ± 0,012 mm, and 0,032 ± 0,029 mm respectively. Exposure variance dose of CdCl2 cause on the decrease area of eyes and the length non-detachment tail significantly (p<0,05).Conclusion: CdCl2 exposure on Danio rerio parental (F1) can decrease area of eyes and length distance non-detachment tail on Danio rerio embryo (F2) (p<0,05).Keywords: Cadmium (CdCl2), Eye area, non-detachment tail, zebrafish (Danio rerio)